2020
DOI: 10.3389/fimmu.2020.01040
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Cytokine Production via Select Packaging and Secretion From Extracellular Vesicles

Abstract: Cytokines are soluble factors that play vital roles in systemic function due to their ability to initiate and mediate cell-to-cell communication. Another important mechanism of intercellular communication that has gained significant attention in the past 10 years is the release of extracellular vesicles (EVs). EVs are released by all cells during normal physiology, in states of resting and activation, as well as during disease. Accumulating evidence indicates that cytokines may be packaged into EVs, and the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 131 publications
(119 reference statements)
2
56
0
Order By: Relevance
“…For instance, cellular activation has been shown to yield higher levels of EV secretion compared to resting cells. This upregulation in EV trafficking has been observed to occur in parallel with increases in intracellular calcium (Ca + ) levels and cytoskeletal remodeling [ 227 , 228 ]. Therefore, the control of intracellular calcium levels may allow for the control of EV release.…”
Section: Treatments Used To Modulate Ev Biogenesis Release and Umentioning
confidence: 99%
“…For instance, cellular activation has been shown to yield higher levels of EV secretion compared to resting cells. This upregulation in EV trafficking has been observed to occur in parallel with increases in intracellular calcium (Ca + ) levels and cytoskeletal remodeling [ 227 , 228 ]. Therefore, the control of intracellular calcium levels may allow for the control of EV release.…”
Section: Treatments Used To Modulate Ev Biogenesis Release and Umentioning
confidence: 99%
“…They may be released from damaged or stressed cells and carry proteins, pathogen-associated and damage-associated molecular patterns, lipids and miRNA, which are encapsulated and thus protected from degrading enzymes [ 14 ]. Cytokines may be selectively sorted to EVs and act as signals to regulate and propagate the immune and inflammatory response [ 15 ]. EV-associated cytokines are different from those released in a soluble form by cells of the same type [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biogenesis of EXs and EMVs, and the triggers for their release from parent cells, are complex biological processes that eventually require the navigation of these vesicles through the extracellular matrix to their extracellular targets which may be near or distant (Barnes and Somerville 2020 [ 7 ]; Birgisdottir and Johansen 2020 [ 41 ]; BriteS 2020 [ 42 ]; Jadli et al, 2020 [ 43 ]). Protein interaction maps have indicated that EX and EMV biolipid boundary membranes have a tendency to interact with discrete extracellular “node” proteins involving surface ligands and delivery receptors, indicating an “ extracellular directional strategy ” for vesicular sorting and translocation over both short and long distances (Choi et al, 2015 [ 44 ]; Leidal and Debnath 2020 [ 45 ]).…”
Section: Extracellular Trafficking Of Ex and Emv Cargomentioning
confidence: 99%